The Effect Of Digital Divide To The Malaysian Economy - Tajudin, Zaima Azfa (2002)
This study is undertaken to evaluate the impact of digital divide to Malaysian economics from March 1996 to March 2002. The method used is through Multiple Linear Regression to test the probable factors of digital divide against ICT Penetration rate. In this study, ICT Penetration rate is used to represent digital divide in inverse relationship.The next method is to determine the effect of digital divide to the ICT industry s profitability by using correlation analysis. Finally, the ICT industry profitability is analyzed on the effect to Malaysian economic (represented by GDP indicator) through correlation analysis.